Transmisi Volatilitas antara Nilai Tukar dan Indeks Harga Saham Gabungan di Pasar Finansial Indonesia: Analisa Setelah Krisis Finansial Asia 1997 - Anhar Fauzan Priyono (Quantitative Economics Journal, 2017)
Volatility of Indonesia Rupiah and Jakarta Composite Index remain one of main issues in Indonesia economy after 1997 Asian crisis. The objectives of this research are (1) determining the volatility of Indonesia Rupiah to US Dollar exchange rates and Jakarta Composite Index (JCI) and (2) analysing the dynamic volatility transmission between exchange rates and JCI. Exchange rate and JCI volatility were measured using GARCH(1,1) approach. Estimated using VAR model, this study found that current volatility of exchange rate (ER) respond significantly to the change of volatility of Jakarta Composite Index (JCI) in the previous 2 months. On the other hand, contribution of JCI volatility to ER is greater than ER volatility to JCI, supporting the portfolio balanced theory.